Tesco targets China - Baack, Daniel W.; Harris, Eric G.; Baack, Donald ([London] : SAGE, 2016)
Tesco was founded in the United Kingdom in the early 20th century as a grocery retailer and has grown to become the third largest retailer in world. The company has a strong international presence, and this case study documents Tesco's strategic plans for further impact in the Chinese market.
Originally Published in: Baack, D. W., Harris, E. G., & Baack, D. (2012). Tesco Targets China. In International marketing (pp. 436-437). Los Angeles: SAGE Publications, Inc. ISBN: 9781452226354.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Tesco (Firm); Strategic planning -- Case studies; Export marketing -- Case studies; International business enterprises -- China -- Case studies